Tiktok as a Language Learning Media: Investigating Students’ Motivational Factors to Learn English at Tadulako University - Marsandah, Marsandah; Budi, Budi; Maghfira, Maghfira; Marhum, Mochtar (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines students' motivation to use TikTok as a language-learning medium and explores how the quality of TikTok content influences their motivation to learn English. The focus is on intrinsic motivations such as enjoyment, curiosity, and personal interest, as well as extrinsic motivations such as academic goals, career preparation, and social recognition. A qualitative research design was chosen, comprising interviews with three students in the English Language Teaching program at Tadulako University. The results showed that the participants used TikTok because of its short, engaging, and interactive video format, which made learning more entertaining and less formal. Intrinsically, they experienced increased interest and satisfaction when engaging with creative English content. Extrinsically, they were motivated by the desire to improve their language skills, achieve academic success, and prepare for a future career as an English teacher. Furthermore, the findings indicated that the quality of TikTok content significantly influenced students' motivation. Clear, concise, and well-structured learning content promotes understanding and confidence, while content that was overly entertainment-oriented or unclear can reduce learning effectiveness. Overall, the study concluded that TikTok could serve as a supportive learning medium when students intentionally selected high-quality educational content to support their language learning goals.